Hummingbird heart - Dandro, Travis, 1974- (Drawn and Quarterly, 2022)
Still reeling from the death by suicide of his drug-addicted father, Travis moves in with his grandmother to become her caretaker as she battles cancer. Meanwhile, he tries to live a typical teen life of pulling pranks, occasional shoplifting, dating, and endless drives through the twisting backroads of Central Massachusetts with Nirvana's Nevermind as the soundtrack. When the police intervene after a prank backfires, the boys realize that their time as children is rapidly disappearing and they may never fully understand each other as they move apart.